Strategic Development of Tourism Based on Local Wisdom in Regional Planning: A Case Study of North and Central Lombok Regencies - Anggara, Jaka; Singandaru, Adhitya Bagus; Husni, Vici Handalusia; Kartikasari, Nungki; Shalehah, Siti Raehanun (Convergence: The Journal of Economic Development, 2024)
Abstract This study aims to design a strategic development plan for tourism based on local wisdom in North Lombok and Central Lombok Regencies, focusing on Sade and Bayan Villages. The research emphasizes the importance of considering the implications of the findings in tourism policies and digital promotion strategies. Data were collected using a mixed-method approach, including in-depth interviews, questionnaires, and field observations. The analysis was conducted using the SWOT and AHP methods to determine strategic priorities. The findings indicate that the main weakness lies in inadequate infrastructure conditions, while the primary strength is the unique appeal of local cultural attractions. Recommended key strategies include improving infrastructure, enhancing public facilities, optimizing digital promotion, and providing training for the local community. These findings offer concrete recommendations for local governments, stakeholders, and tourism business operators in supporting the sustainable management of local wisdom-based tourism. Keywords : Local Wisdom-Based Tourism, Regional Planning, SWOT Analysis, AHP Analysis. Abstrak Penelitian ini bertujuan untuk merancang rencana pengembangan strategis pariwisata berbasis kearifan lokal di Kabupaten Lombok Utara dan Kabupaten Lombok Tengah, dengan fokus pada Desa Sade dan Desa Bayan. Studi ini menekankan pentingnya mempertimbangkan implikasi temuan dalam kebijakan pariwisata serta strategi promosi digital. Pengumpulan data dilakukan dengan pendekatan metode campuran (mixed-method), yang mencakup wawancara mendalam, kuesioner, dan observasi lapangan. Analisis data dilakukan menggunakan metode SWOT dan AHP untuk menentukan prioritas strategis. Hasil penelitian menunjukkan bahwa kelemahan utama terletak pada kondisi infrastruktur yang kurang memadai, sementara kekuatan utama adalah daya tarik unik dari budaya lokal. Strategi utama yang direkomendasikan mencakup peningkatan infrastruktur, pengembangan fasilitas publik, optimalisasi promosi digital, serta pemberian pelatihan bagi masyarakat lokal. Temuan ini memberikan rekomendasi konkret bagi pemerintah daerah, pemangku kepentingan, dan pelaku usaha pariwisata dalam mendukung pengelolaan pariwisata berbasis kearifan lokal secara berkelanjutan. Kata kunci: Pariwisata Berbasis Kearifan Lokal, Perencanaan Wilayah, Analisis SWOT, Analisis AHP.